Atributos químicos de latossolo vermelho submetido a diferentes manejos - de Freitas, Ludmila [UNESP] (2015)
The removal of natural vegetation for establishing an agricultural system may lead to soil imbalances according to management system used. Three adjacent areas were selected in Guariba, SP, Brazil, for the purpose of studying changes in a Latossolo Vermelho Distrófico (oxisol) caused by continuous cropping of sugarcane. In each area, four samples were collected in the 0.0-0.10 m and 0.10-0.20 m soil layers. The following chemical properties were evaluated: pH, organic matter (OM), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), aluminum (Al), potential acidity (H+Al), and aluminum saturation (m%); and the values of the sum of bases (SB), cation exchange capacity (CEC), and base saturation (V%). Cluster analyses and principal components allowed identification the formation of three groups, made up of native forest, reforested area, and the area planted to sugarcane. Results indicate that intensive use of the soil altered its chemical properties. Multivariate analysis techniques showed that the main properties related to the environment in the native forest area were organic matter, potential acidity, aluminum saturation, and aluminum. In the sugarcane area the properties were Mg, Ca, V%, BS, SB, and CEC. The reforested area was in an intermediate position between the native forest and sugarcane environments.